LEACH ARCILLAS ACTIVATED PARTIAL ACID SULFURICO - Romero Y Otiniano, P. (1998)
This work is concerned with the activation of calcium bentonite from Junín- Perú (with a moisture content of 24.1% and an average of particle size 40 µ ) with sulphuric acid. The parameters studied are the ratio of bentonite to acid solution, acid concentration and reaction time to boiling temperatura of the mixture. The optimum conditions obtained are the following: 0.47 kg. of bentonite/kg. of acid solution to 4.8 N, 4 h of treatment to 104 ºC and the conversion of 45.6% alumina and 73.5% of sulphuric acid.